Vitiligo Lateral Lower Lip - Sahoo Antaryami; Singh Prabhas Chandra; Patnaik Satyadarsi; Singh Nilachal; Srichandan Managobinda (Wolters Kluwer Medknow Publications, 2002)
Vitiligo characteristically affecting the lateral lower lip (LLL) is a common presentation in South Orissa. This type of lesion has rarely been described in literature. One hundred eighteen such cases were studied during the period from October 1999 to September, 2000. LLL vitiligo constituted 16.39% of all vitiligo patients. Both sexes were affected equally. The peak age of onset was in the 2nd decade, mean duration of illness 21.46 months. Fifty six patients had unilateral lesion (38 on the left and 18 on the right). Among the 62 patients having bilateral lesions, the onset was more frequent on the left (38) than either the right (8) or both sides together (16). All the patients were right handed. Association with local factors like infection, trauma, cheilitis, FDE etc were associated in 38.98% of cases, but systemic or autoimmune diseases were not associated. Positive family history was found in 22% of cases.